2020
DOI: 10.1002/adtp.202000123
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles Loaded with Wnt and YAP/Mevalonate Inhibitors in Combination with Paclitaxel Stop the Growth of TNBC Patient‐Derived Xenografts and Diminish Tumorigenesis

Abstract: Triple negative breast cancer (TNBC) accounts for the majority of breast cancer‐related deaths and remains the hardest breast cancer to treat due to the lack of specific therapeutic targets. While chemotherapy is the mainstay of systemic treatment for TNBC, it is associated with chemotherapy‐induced cancer stem cells (CSCs) and tumor regeneration. Here, it is found that Wnt and YAP target genes that have been closely associated with CSCs are highly expressed in TNBC patient tumors and negatively correlated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…Similarly, our own research has been demonstrated in TNBC in vivo mouse models using patient-derived xenografts (patient tumors implanted immediately and only as solid tumors into immunocompromised mice) that post-chemotherapy exposure led to increased CD44 + /CD24 -and ALDH high CSC populations [64]. Afterward using a serial dilution assay (the gold standard for functional tumorigenicity) it was found that compared to the control, chemotherapy-treated PDX tumors demonstrated enhanced tumor formative capabilities (forming tumors at a rate of 80% upon injection of 1,000,000 cells versus the control which formed tumors at a rate of 20% with an injection of 1,000,000 cells) [64]. These studies demonstrate that chemotherapy-induced CSC enrichment represents a major factor in relapse and tumor reconstitution.…”
Section: Clinical Importance Of Cscs In Tnbcmentioning
confidence: 61%
See 1 more Smart Citation
“…Similarly, our own research has been demonstrated in TNBC in vivo mouse models using patient-derived xenografts (patient tumors implanted immediately and only as solid tumors into immunocompromised mice) that post-chemotherapy exposure led to increased CD44 + /CD24 -and ALDH high CSC populations [64]. Afterward using a serial dilution assay (the gold standard for functional tumorigenicity) it was found that compared to the control, chemotherapy-treated PDX tumors demonstrated enhanced tumor formative capabilities (forming tumors at a rate of 80% upon injection of 1,000,000 cells versus the control which formed tumors at a rate of 20% with an injection of 1,000,000 cells) [64]. These studies demonstrate that chemotherapy-induced CSC enrichment represents a major factor in relapse and tumor reconstitution.…”
Section: Clinical Importance Of Cscs In Tnbcmentioning
confidence: 61%
“…This is highlighted by Creighton et al who demonstrated that in post-chemotherapy breast cancer patients there were increased CD44 + /CD24 -CSCs populations compared to the proportion present before treatment [60]. In breast cancer tissue samples post-letrozole treatment, it was found that there was an increase in FN1, SNAI2, VIM, FOXC2, MMP2, and MMP3 (mesenchymal related genes) as well as diminished CDH1 (an epithelial related gene) suggesting an enrichment of mesenchymal properties and EMT (epithelial to mesenchymal transition), a process through which epithelial cells gain mesenchymal properties which correlate into enhanced migration and invasion properties allowing for increased metastasis in cancer models [51,56,[60][61][62][63][64]. This report demonstrated clinical evidence that post-chemotherapy, CSCs can be enriched and gain a mesenchymal phenotype in breast cancer models [60].…”
Section: Clinical Importance Of Cscs In Tnbcmentioning
confidence: 99%
“…Similarly, our own research has been demonstrated in TNBC in vivo mouse models using patient-derived xenografts (patient tumors implanted immediately and only as solid tumors into immunocompromised mice) that post-chemotherapy exposure led to increased CD44 + /CD24 -and ALDH high CSC populations [70]. Afterwards, using a serial dilution assay (the gold standard for functional tumorigenicity), it was found that compared to the control, chemotherapy-treated PDX tumors demonstrated enhanced tumor formative capabilities (forming tumors at a rate of 80% upon an injection of 1,000,000 cells versus the control, which formed tumors at a rate of 20% with an injection of 1,000,000 cells) [70]. These studies demonstrate that chemotherapy induced CSC enrichment represents a major factor in relapse and tumor reconstitution.…”
Section: Clinical Importance Of Cscs In Tnbcmentioning
confidence: 61%
“…This is highlighted by Creighton et al who demonstrated that in post-chemotherapy breast cancer patients there was an increased frequency of CD44 + /CD24 -CSCs populations compared to the proportion present before treatment [66]. In breast cancer tissue samples post-letrozole treatment it was found that there was an increase in FN1, SNAI2, VIM, FOXC2, MMP2, and MMP3 (mesenchymal-related genes) as well as diminished CDH1 (an epithelial-related gene) suggesting an enrichment of mesenchymal properties and EMT (epithelial to mesenchymal transition) [57,62,[66][67][68][69][70]. EMT is a process through which epithelial cells gain mesenchymal properties which correlate into enhanced migration and invasion properties allowing for increased metastasis in cancer models [57,62,[66][67][68][69][70].…”
Section: Clinical Importance Of Cscs In Tnbcmentioning
confidence: 99%
See 1 more Smart Citation